Institutional characteristics and effects of confirmation hearing in Korea. (1st October 2016) - Shin, Hyunki
Abstract: This article analyzes how Korean confirmation hearings affect the quality of high-level executive branch officials appointed by a president, based on the criteria of patronage and merit. An ordered logit regression analysis was conducted on the patronage and merit of the 409 high-ranking officials appointed during the Kim Young-sam to Lee Myung-bak Administrations. The results showed that confirmation hearings did not have any effect on the patronage of high-ranking officials, but did have the effect of increasing their merit. This is probably because presidents tended to select candidates with high merit after the introduction of the confirmation hearings in order to persuade the National Assembly. These findings show that despite the institutional superiority of president, who can force appointments through in spite of the Assembly's objection, and dysfunctional management resulting from partisan conflicts, the two authorities do compromise with each other.